STUDI EPIDEMIOLOGIS STRES, TOLERANSI STRESS DAN STRESSOR PSIKOSOSIAL PADA PELAJAR SEKOLAH LANJUTAN ATAS DI KOTA GORONTALO - Jusuf, Muhammad Isman; Paramata, Nanang; Abudi, Ramli (Jurnal Health and Sport, 2012)
Stress can be one of the social change impact and be one of the effect modernization usually followed by technology proliferation, migration to the city and individual competition. Among student of senior high school, this individual competition is very incessant especially in the field of education and chance work. student of senior high school is very susceptible experience stress This study aims to know insidence of stress in student of senior high school at Gorontalo city and to detect stres, stress tolerance dan psychososial stressor. This is a crossectional study. Data are taken from students senior high school, with consecutive sampling. Research is conducted with questioner. Average student were not invulnerable towards stress with presentase each 95.2% for first class, 96.3% for second class and 96.6% for third class. For student at first and third class at most experience stresor light with presentase 29.6% and 29.7%. to second class at most experience a little stresor with presentase 22%. This study concludes that incidence of stress is 62.3%. average student of senior high school at Gorontalo city were not invulnerable towards stress. Student at first and third class were most experience stressor light at second classs were most experience a little stress.